Investigating the influence of sample size on measurement of collapse of gypseous soil - Hassan Al-Riahi S.M.; Pauzi N.I.M.; Fattah M.Y. (Elsevier B.V., 2025)
This study aims to analyze the behavior of soils containing gypsum, specifically focusing on the impact of gypsum content and different soil parameters. Several physical tests and assessments were conducted on synthetic gypseous soil, which consists of silty clay and different proportions of gypsum (20%, 40%, and 60%). The research emphasizes the notable influence of gypsum concentration on soil collapsibility, whereby higher levels of gypsum are associated with a heightened propensity for collapse. The soil behavior is significantly influenced by various factors, including but not limited to the initial void ratio, total unit weight, and degree of saturation. Quantitative predictive models have been constructed to describe these interactions, offering significant tools for engineers and researchers engaged in the study of gypseous soils. Furthermore, this study provides insights into the intricate patterns of human settlement throughout history, focusing on the significance of gypsum bonding and unit weight in reducing soil settlement. The results demonstrate that the single oedometer test exhibits greater collapse potential values at 200 kPa compared to the double oedometer test, showing an increase of 27% and 44%, respectively. The observed discrepancy can be ascribed to softening and gypsum dissolving, which commence before reaching a pressure of 200 kPa in the double oedometer test. Moreover, the research presents a modified collapse test with a more dependable methodology for identifying collapsible gypseous soil in contrast to conventional techniques. The proposed methodology entails employing larger sample sizes and achieving complete particle saturation by upward water flow, mitigating the drawbacks observed in traditional methodologies, namely inadequate sample sizes and incomplete particle saturation. In general, this study greatly enhances our comprehension of the mechanics of gypseous soil and offers useful methodologies for evaluating and addressing soil collapsibility in geotechnical and building endeavors. ? 2024